A Secure Base Responsive Support of Goal Strivings and Exploration in Adult Intimate Relationships. (article). - Feeny, Brooke C.
A theoretical framework is proposed for examining the interpersonal processes involved in the support of a relationship partners' goal striving, personal growth, and exploratory behavior, and for examining consequences of receiving either responsive or unresponsive support in this domain. These processes were examined using both observational and experimental methods. In phase 1, couples were videotaped as they discuss personal for the future. In Phase 2, support behavior was experimentally manipulated to examine immediate effects on the recipient. Results indicated that responsive (nonintrusive) support of a relationship partners' goal strivings and explorations have important implications for the recipients happiness, self-esteem, and perceived likelihood of achieving specific goals. The importance of research examining this type of support is discussed. -- (from the author). -- ( from the author).